Dendritic polarizing agents for DNP SENS. Issue 1 (1st September 2016) - Liao, Wei-Chih; Ong, Ta-Chung; Gajan, David; Bernada, Florian; Sauvée, Claire; Yulikov, Maxim; Pucino, Margherita; Schowner, Roman; Schwarzwälder, Martin; Buchmeiser, Michael R.; Jeschke, Gunnar; Tordo, Paul; et al.
Abstract : Dendrimer-shielded polarizing agents for the application of DNP SENS to reactive surfaces. Abstract : Dynamic Nuclear Polarization Surface Enhanced NMR Spectroscopy (DNP SENS) is an effective method to significantly improve solid-state NMR investigation of solid surfaces. The presence of unpaired electrons (polarizing agents) is crucial for DNP, but it has drawbacks such as leading to faster nuclear spin relaxation, or even reaction with the substrate under investigation. The latter can be a particular problem for heterogeneous catalysts. Here, we present a series of carbosilane-based dendritic polarizing agents, in which the bulky dendrimer can reduce the interaction between the solid surface and the free radical. We thereby preserve long nuclear T ′2 of the surface species, and even successfully enhance a reactive heterogeneous metathesis catalyst.